2019
DOI: 10.1001/jama.2019.0693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Catheter Ablation vs Antiarrhythmic Drug Therapy on Mortality, Stroke, Bleeding, and Cardiac Arrest Among Patients With Atrial Fibrillation

Abstract: IMPORTANCE Catheter ablation is effective in restoring sinus rhythm in atrial fibrillation (AF), but its effects on long-term mortality and stroke risk are uncertain. OBJECTIVE To determine whether catheter ablation is more effective than conventional medical therapy for improving outcomes in AF. DESIGN, SETTING, AND PARTICIPANTS The Catheter Ablation vs Antiarrhythmic Drug Therapy for Atrial Fibrillation trial is an investigator-initiated, open-label, multicenter, randomized trial involving 126 centers in 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
826
6
53

Year Published

2019
2019
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 1,139 publications
(978 citation statements)
references
References 37 publications
35
826
6
53
Order By: Relevance
“…Recently, Packer et al reported that the composite endpoints of mortality and cardiovascular hospitalization exhibited a significant 17% relative lower event rate for the CA group than medical therapy group. To improve the mortality as well as quality of life, CA might be aggressively considered especially in patients with heart failure or a stroke history …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Packer et al reported that the composite endpoints of mortality and cardiovascular hospitalization exhibited a significant 17% relative lower event rate for the CA group than medical therapy group. To improve the mortality as well as quality of life, CA might be aggressively considered especially in patients with heart failure or a stroke history …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the impact of CA has been greater in patients with an age of <65 years old, heart failure of <NYHA functional class II, and EF of ≧ 25%. The CABANA study also reported that the impact of CA was greater in patients with an age of <65 years old . Those two RCTs indicated the importance of early intervention to maintain sinus rhythm by CA in patients with AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CABANA study had a lower rate of disabling strokes in the catheter ablation group compared to the drug therapy group, but there was no significant difference (0.3% vs 0.6%, P = .1). The rate of major bleeding was almost the same between the two groups (3.2% vs 3.3%, P = .7) . The high‐performing rate of catheter ablation and discontinuation of anticoagulation therapy after catheter ablation might lead to a lower stroke/systemic embolism and major bleeding rate in the HAF‐NET Registry.…”
mentioning
confidence: 87%
“…The HAF‐NET Registry showed that catheter ablation reduced the cardiac events requiring hospitalization. In a randomized trial, the CABANA study presented a reduction in the mortality or cardiovascular hospitalizations in the catheter ablation group . The CATLE‐AF study also showed that catheter ablation reduced hospitalizations for worsening heart failure .…”
mentioning
confidence: 97%